Water in a hydrophobic environment and the effect of some organic substances on it - V. V. Turov; T. V. Krupska (Хімія, фізика та технологія поверхні)
The structure of water in the interparticle gaps of methyl silica was investigated using the method of low-temperature 1H NMR spectroscopy. It is shown that the main part of the interfacial water is in the form of large clusters, or nanodroplets, which freeze at a temperature of about 273 K. After freezing of this water, signals of strongly and weakly associated water are observed in the spectra, which melts at temperatures of 215–368 K. It is likely that the freezing of weakly associated of water occurs through the formation of clusters in which closely spaced water molecules interact not through hydrogen bonds, but through dipole-dipole interactions. In the presence of chloroform, the amount of weakly associated water increases several times. This is explained by the possibility of formation of chloroform hydrates, in which the mobility of water molecules is approximately the same as in strongly associated water clusters. If joint adsorption of chloroform and methane occurs on the hydrated surface of methyl silica, under the influence of CH4, weakly mobile weakly associated water is transformed into methane hydrates in quasi-liquid and solid states, while only mobile forms of hydrates are recorded in the spectra. DMSO reduces the possibility of formation of weakly associated water, but a certain amount of it is fixed even in the medium of liquid DMSO. At the same time, the freezing of water in systems containing DMSO occurs at much lower temperatures due to solvation of water and DMSO molecules. The difference in interphase energy in air and in organic media determines the solvation energy.